Inside Cover: From Trash to Treasure: Turning Air Pollutants into Materials for Energy Storage (ChemNanoMat 6/2017). Issue 6 (11th May 2017) - Liang, Jiachen; Zhang, Chen; Liu, Donghai; Zhang, Lina; Ling, Guowei; Yang, Quan‐Hong
Abstract : New energy‐storage and pollution‐reduction techniques are needed to reduce potential environmental problems. Combining air pollutant reduction with energy‐storage devices is thus an appealing solution. In this work, the principles of recovering air pollutants for use in energy‐storage materials are proposed, including their direct use as active materials, their conversion into active materials, and their use as dopants to modify the electrode. More information can be found in the Focus Review by G. Ling, Q.‐H. Yang et al. onpage 392 in Issue 6, 2017 (DOI:10.1002/cnma.201700038 ).